MEDIA EDUKASI E-BOOKLET BERBASIS AUGMENTED REALITY MENGENAI POLA MAKAN SEHAT PENCEGAHAN DIABETES MELITUS TIPE 2 - Sofyan, Aqilah Nafisa; Karjatin, Atin (Jurnal Kesehatan Siliwangi, 2024)
Background:  The prevalence of diabetes melitus in Indonesia is 1,017,290, West Java in 2022 is 2,124,068, Cianjur in 2023 is 13,400, and the Sukasari Cilaku health center area is 650, thus it is necessary to increase knowledge about the causes, which are closely related to unhealthy eating behavior. Based on the results of research, augmented  reality-based e-booklet educational media can help increase adolescents' knowledge. Objective: To determine the feasibility  of augmented reality-based e-booklet educational media with a 4D approach. Methods: Research methods with a 4D approach, namely, define, design, development with material tests, media tests, small-scale tests and statistical tests with a quantitative approach using a type of quasi experiment research with a one-group pretest-posttest design design to 81 students, as well as dissemination. Results: Needs analysis based on a preliminary study of media, the goal requires material that is outlined in  augmented  reality-based e-booklet educational media, with A5 size, consisting of 20 pages, blue, in which there are materials and pictures, and using Indonesian. Development with statistical tests obtained media suitable for use and has an influence on knowledge. Media can be accessed via links and qr codes. Conclusion: Augmented reality-based e-booklet educational media  is feasible and can be accessed at the https://bit.ly/ebookletpolamakansehat link.